PENGARUH AMBIENT MARKETING DAN VIRAL MARKETING TERHADAP BRAND AWARENESS (STUDI KASUS KAMPANYE TRIV CRYPTO EXCHANGE “STAKING CRYPTO, TIDUR DAPAT DIVIDEN”) - Shafira Ratna Surya Ningrum; Sri Widyastuti; Yuli Ardianto; Adi Nugroho (JIMP : Jurnal Ilmiah Manajemen Pancasila, 2026)
The intensifying competition in the cryptocurrency industry is compelling companies to develop unconventional marketing strategies to enhance brand awareness, particularly targeting Generation Z. This study aims to analyze the impact of ambient marketing and viral marketing on brand awareness in TRIV's campaign “Staking Crypto and Earn Dividends While You Sleep”. This study adopted a quantitative approach using a descriptive explanatory methodology based on a questionnaire survey of 150 respondents selected via purposive sampling. Data were analyzed using validity verification, reliability verification, classical assumption verification, and multiple linear regression analysis. The research findings indicate that public space marketing and viral marketing influence brand awareness partially and simultaneously, with viral marketing emerging as the dominant variable. This finding supports the effectiveness of integrating unconventional marketing strategies with viral content for enhancing brand awareness within the cryptocurrency industry.